The complexity of processing tree queries in distributed databases - Chihping Wang (Parallel and Distributed Processing, 2nd IEEE Symposium On, 1990)
Semi-joins have been introduced to reduce the cost of processing distributed queries. The determine the optimal semi-join processing strategy, one must consider both the reduction effect and the transmission overhead. Researchers have studied the problem of finding the optimal semi-join strategies for processing tree queries. Although a number algorithms have been proposed, they either have a very high complexity or only solve special cases. It is conjectured that the tree query processing problem is inherently difficult. The author formally answers this question by proving it NP-hard.< >